2017
DOI: 10.18632/oncotarget.14447
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryotic elongation factor 2 is a prognostic marker and its kinase a potential therapeutic target in HCC

Abstract: Hepatocellular carcinoma is a cancer with increasing incidence and largely refractory to current anticancer drugs. Since Sorafenib, a multikinase inhibitor has shown modest efficacy in advanced hepatocellular carcinoma additional treatments are highly needed. Protein phosphorylation via kinases is an important post-translational modification to regulate cell homeostasis including proliferation and apoptosis. Therefore kinases are valuable targets in cancer therapy. To this end we performed 2D differential gel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 47 publications
1
28
0
Order By: Relevance
“…A recent study showed that high levels of total eEF2 and P-eEF2 are associated with poor prognosis of HCC patients. 9 Here, we demonstrate for the first time that inhibition of eEF2K prevents HCC angiogenesis and progression in an HCC xenograft tumor model, indicating that pharmacologically targeting eEF2K may be a promising therapeutic strategy against HCC, and as well other types of angiogenic solid tumors.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…A recent study showed that high levels of total eEF2 and P-eEF2 are associated with poor prognosis of HCC patients. 9 Here, we demonstrate for the first time that inhibition of eEF2K prevents HCC angiogenesis and progression in an HCC xenograft tumor model, indicating that pharmacologically targeting eEF2K may be a promising therapeutic strategy against HCC, and as well other types of angiogenic solid tumors.…”
Section: Discussionmentioning
confidence: 66%
“…Previously, it has been reported that the relative abundances of total and phosphorylated (at Thr56) eEF2 are higher in HCC tissues compared to adjacent nontumor tissues or normal liver tissues. 9 We first compared the levels of eEF2K and phospho (p-) eEF2 Thr56 among different HCC cell lines. MHCC97H cells exhibited highest levels of both eEF2K and p-eEF2 Thr56 (Zhou Y and Shen K, unpublished data).…”
Section: Inhibition Of Cell Proliferation Migration and Invasion In mentioning
confidence: 99%
See 2 more Smart Citations
“…The most common method is to use a single sgRNA targeted to a critical exon in order to introduce indels, likely causing a frameshift mutation and/or NMD (figure 2A). This approach has been used to validate, in vitro, potential oncogenes discovered in human liver cancers, such as acid sensing ion channel 1a43 and eukaryotic elongation factor 2 kinase 44. Similarly, isocitrate dehydrogenase 1, commonly mutated in intrahepatic cholangiocarcinoma,45 has been deleted in the HepG2 cell lines to dissect its biological and metabolic functions 46…”
Section: Introductionmentioning
confidence: 99%